Michalskiite, Cu2+Mg3Fe3+3.33(VO4)6, an Mg analogue of lyonsite, from the Ronneburg uranium deposit, Thuringia, Germany - Kampf,A.R.; Plasil,J.; Skoda,R.; Cejka,J. (Journal of Geosciences, 2022)
Michalskiite (IMA2019-162), Cu2+Mg3Fe3+3.33(VO4)6, is a new mineral found on specimens from the dump of the Lichtenberg open pit, Ronneburg uranium mining district, Thuringia, Germany. It is a secondary mineral occurring with arcanite, epsomite, hematite and syngenite on matrix consisting of fine-grained quartz, K-feldspar and mica. It forms striated prisms and needles, elongated on [001], up to about 0.2 mm long. Crystals are brown-red with a light orange streak. They are transparent and have adamantine lustre. The mineral is brittle with curved fracture, very good {001} cleavage and a Mohs hardness of ˜3½. The calculated density is 3.848 g.cm-3 based on the empirical formula. The new mineral is biaxial (-), with 2Vmeas = 49(1)°. No pleochroism was observed. Optical orientation is X = c. The empirical formula of michalskiite (on the basis of 24 O apfu) is (Cu2+1.31Mg2.76Fe3+2.75Al0.21Ni0.16Ti4+0.14Mn3+0.06Zn0.01)Σ7.40(V5+5.96Si0.02)Σ5.98O24. The Raman spectrum is dominated by the vibrations of VO43- units. Michalskiite is orthorhombic, Pmcn, a = 10.2356(9), b = 17. 3689(16), c = 4.9406(4) Å, V = 878.35(13) Å3 and Z = 2. The five strongest powder X-ray diffraction lines are [dobs, Å (I, %) (hkl) ]: 3.27 (100) (221,150), 2.74 (40) (241,151), 2.52 (50) (331), 1.55 (30) (282), 1.42 (25) (063). The crystal structure of michalskiite was refined from the single-crystal X-ray data to R = 0.0386 for 888 independent observed reflections, with Iobs > 2σ(I). Michalskiite is isostructural with lyonsite; however, the Cu2 site in the lyonsite structure is split into M2 and M2’ sites in the michalskiite structure with Mg occupying the M2’ site. The new mineral name honours German mineral collector and dealer Dipl. Min. Steffen Michalski, who discovered this mineral.
Keywords: michalskiite; new mineral; lyonsite; crystal structure; Raman spectroscopy